Sertifikasi Halal Sebagai Bagian Strategi Ekonomi Pemerintahan Shinzo Abe - Erni Puspitasari; Indun Roosiani (IDEA : Jurnal Studi Jepang, 2021)
ABSTRACT: During the Shinzo Abe goverment, Japan began to take part in the halal industry as a diversification of state revenues. The aims of this study is to analyse the background of Japanese halal product certification related to the economical strategy of the Shinzo Abe government. The research method used is descriptive qualitative. The results show that there are various backgrounds why Japan conduct halal certification on its products, among others the decreasing of Japan population then resulting in a decrease in the level of food consumption, meanwhile Japanese Muslims and world Muslims have incerased sharply from year to year so that it has an impact on the increasing level of demand for halal products, the emergence of the trend of halal living, and the high world halal market. For this reason, Japan conducts halal certification for its products as a condition in order to be able to distribute its products not only domestically but also abroad. Various strategies were carried out by Japan in introducing its halal products, among others, by involving small and medium enterprises, foreign cooperation, various exhibitions, and various halal seminars and educations.